(untitled) (Costos y Gestión, 2020)
The economic activities of the different productive chains generate, from their origin to the final consumption of the products, emission of gases that produce an environmental footprint that can be measured and compensated, but that cause a global warming that impacts on the quality life for the society. One way to measure environmental health is through the emission of greenhouse gases, known as “carbon footprint”. This has become an instrument that contributes to society having a socially responsible behavior, developing less aggressive actions for the environment and more sustainable in the long term. However, few companies in Argentina dedicate time and resources to measuring the impact generated by the emission of gases, much less even those that work to reduce it. From a mesoeconomic approach we seek to identify, quantify and characterize the potential environmental impact of the average economic aggregates on the determination of the normalized cost, so that from the General Theory of Cost becomes a tool of sustainability. This will be achieved through the consideration of greenhouse gas emissions in the determination of the normalized physical component of the medium cost, which implies incorporating ecoefficiency into the analysis scheme, through environmental necessity. This generates a contribution to the information system for sustainability and environmental sustainability that is proposed to add to the uses of the General Theory of Cost. Knowing the effect that gas emissions produce through the production processes of the average economic aggregates implies knowing the responsibility for the environmental impacts that they provoke in the search for sustainability and sustainability of the system